CFD simulations of a wind turbine for analysis of tip vortex breakdown. (September 2016) - Kimura, K; Tanabe, Y; Aoyama, T; Matsuo, Y; Arakawa, C; Iida, M
Abstract: This paper discusses about the wake structure of wind turbine via the use of URANS and Quasi-DNS, focussing on the tip vortex breakdown. The moving overlapped structured grids CFD Solver based on a fourth-order reconstruction and an all-speed scheme, rFlow3D is used for capturing the characteristics of tip vortices. The results from the Model Experiments in Controlled Conditions project (MEXICO) was accordingly selected for executing wake simulations through the variation of tip speed ratio (TSR); in an operational wind turbine, TSR often changes in value. Therefore, it is important to assess the potential effects of TSR on wake characteristics. The results obtained by changing TSR show the variations of the position of wake breakdown and wake expansion. The correspondence between vortices and radial/rotational flow is also confirmed.